Studies on the sulphatases - Roy, Alexander Bilton (The University of Edinburgh, 1957)
1. The Sulphatase of Ox Liver. 1. The complex nature of the enzyme. Roy, A.B. (1953). Biochem. J. 53, 12. • 2. The Sulphatase of Ox Liver. 2. The purification and properties of sulphatase A. Roy, A.B. (1953). Biochem. J. 55, 653. • 3. The Sulphatase of Ox Liver. 3. Further observations on sulphatase B and an investigation of the origin of fractions A and B. Roy, A.B. (1954). Biochem. J. 57, 465. • 4. The intracellular Distribution of Sulphatase. Roy, A.B. (1954). Biochim. Biophys. Acta, 14, 149. • 5. The Sulphatase of Ox Liver. 4. A note on the inhibition of sulphatases A and B. Roy, A.B. (1955). Biochem. J. 59, 8. • 6. The Sulphatase of Ox Liver. 5. Sulphatase C. Roy, A.B. (1956). Biochem. J. 64, 651. • 7. The Sulphatase of Ox Liver. 6. Steroid sulphatase. Roy, A.B. (1957). Biochem. J. (In the press). • 8. The Kinetics of Sulphatase A. Roy, A.B. (1956). Biochem. J. 62, 35P. • 9. The Occurrence of Nitropyrogallol Disulphate in Preparations of Nitrocatechol Sulphate. Roy, A.B. & Kerr, L.M.H. (1956) Nature, 178, 376. • 10. The Kinetics of Sulphatase A. Roy, A.B. (1957). Exper. 13, 32. • 11. The Steroid Sulphatase of Patella vulgata. Roy, A.B. (1954). Biochem. Biophys. Acta, 15, 300. • 12. The Steroid Sulphatase of Patella vulgata. Roy, A.B. (1956). Biochem. J. 62, 41. • 13. The Enzymic Synthesis of Steroid Sulphates. Roy, A.B. (1956). Biochem. J. 63, 294. • 14. Le Métabolisme des Sulfates de Stéroïdes. Roy, A.B. (1957). Colloquium on the Biochemistry of Sulphur, Roscoff.